LEGAL CONSEQUENCES AND NOTARY LIABILITY FOR DEEDS THAT ARE DEFECTED BY LAW (Lex Jurnalica, 2023)
In relation to the profession of a notary in making a deed, it will of course be related to responsibility. The responsibility of a notary is not only in the process of making an authentic deed, but until the authentic deed is realized until after the authentic deed is formed. In principle, the deed made by a notary is an authentic deed, but in practice the authentic deed can turn into a private deed for various reasons. When the authentic deed is declared invalid by the court, which is caused by the non-fulfillment of the legal requirements for making the authentic deed which then causes harm to the parties, the notary can be held accountable. What are the legal consequences of a legally flawed deed? What is the notary's responsibility for a legally flawed deed? The legal consequences of a legally flawed deed can be degraded into a private deed if the deed contains a violation as regulated in Article 1869 of the Civil Code. Accountability of a notary to a legally flawed deed, a notary can be held accountable for administrative, civil and criminal liability if it is proven that he has made a mistake in carrying out his position as a public official who makes an authentic deed.